Propuesta para la sustitución de insumos en la obtención del biofungicida “antígonic”, dejando como ingrediente activo Trichoderma harzianum para la empresa Gestores del Campo S.A.S. (2020)
In recent years, environmental sustainability has become a priority, for this reason new companies have begun to penetrate the agricultural market more and more, knowing that only those that provide the best characteristics, efficiencies and costs will be the ones that take the lead. most of the market. Gestores del Campo S.A.S is a company that is dedicated to the commercialization of bio-inputs for agricultural use which recognizes its potential and is in constant productive improvement in order to increase the demand for its products. It is for this reason that Antígonic, a biofungicide present in its product portfolio, is chosen to evaluate the economic viability of the substitution of inputs that represent a high cost without actually altering its chemical structure. The main objective of this work was to develop a proposal for the replacement of inputs in obtaining the Antígonic biofungicide with Trichoderma harzianum as an active ingredient in order to be able to take advantage of the diversity in inputs that the world has at the green ecology level and thus generate an economic estimate that this company could improve, so initially a diagnosis was made to the company Gestores del Campo SAS to determine the current state of the process and thus be able to make an estimate of which are the raw materials that could be replaced within the which were found: sources of carbon, nitrogen, salts, oils and surfactants.